Reforming the Public Expenditure System in Korea - Nam, Young-Sook (OECD Economics Department Working Papers, 2003)
Although Korea has the second-lowest level of public spending among OECD countries at 22½ per cent of GDP, it faces strong upward spending pressures over the medium and longer term, which could threaten fiscal sustainability. This paper analyses the main features of Korea's public expenditure system and reviews expenditure trends and the main forces behind them. The objective is to identify the major shortcomings in budget planning, management and control systems that have impeded better public sector performance. The paper concludes by proposing policy measures to enhance the effectiveness, efficiency and transparency of the public expenditure management system. These include managing public finance within a medium-term expenditure framework; making the budgetary system more comprehensive and transparent by consolidating special accounts and public funds and bringing extra-budgetary funds into the budget; introducing more flexible and results-focused public management to improve ...